Spring-cleaning of African agathidines: new combinations for five species previously placed in Cremnops Förster (Hymenoptera: Braconidae) - Tucker, Erika M.; Sharkey, Michael J. (Zootaxa, 2015)
Little work has been done with the African species of Cremnops since their original descriptions. Herein we propose new combinations for five species that are currently placed in Cremnops, i.e., C. atripennis Szépligeti 1914 and C. elegantissima Szépligeti 1908 are moved to Disophrys; C. borealis (Szépligeti 1914) and C. rubrigaster Masi 1944 are moved to Biroia; and C. pulchripennis Szépligeti 1905 is moved to and renamed Biroia neopulchipennis. These changes result in Disophrys atripennis (Szépligeti 1915) becoming a jr. homonym, which we change to Disophrys szatripennis. Additionally, two species are proposed as nomen dubia: C. rufitarsis Szépligeti 1913 and C. schubotzi Szépligeti 1915.